Costs of implementing and managing cut sunflower in an organic planting system in the Municipality of Laranjeiras do Sul, State of Paraná (PR), Brazil (Research, Society and Development, 2024)
The flower market is constantly expanding in Brazil, demanding more and more quality in the products sold. The cultivation of ornamental cut sunflower (Helianthus annuus L.) is included in the categories of expanding flowers in the country and its organic cultivation is a possibility of generating income, but there are few studies on its economic aspects Therefore, the objective of this research was to determine the main technical coefficients and costs of implementing and managing 0.5 hectares of cut sunflower in an organic production system in Laranjeiras do Sul/PR. Thus, the study was divided into three distinct stages. The first was carried out through bibliographical research, aiming to outline the aspects of planting cut sunflowers in an organic plantation, highlighting their processes and needs. The second stage of the research refers to carrying out the installation of an experiment with the aim of validating the proposed study. Finally, the third stage refers to the determinations of the main technical coefficients and their costs. The summary of the cost results for the implementation and management of 0.5 hectare of sunflower for ornamental cutting in an organic system in the region of Laranjeiras do Sul were R$: 190,757.40, with the largest expenses being related to inputs (97, 71%), then referring to mechanized operations (1.31%), manual operations (0.92%) and finally with other inputs representing 0.05%. The most significant components of the cost were inputs, which added up to greater values in the experiment installation process.